2001
DOI: 10.1007/bf02873592
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of berberine and santonin on spore germination of some fungi

Abstract: Berberine and santonin were isolated from rhizomes of Berberis aristata and unexpanded flower buds of Artemisia maritima, respectively. Efficacy of these two chemicals individually as well as of their mixtures, was tested against spore germination of some saprophytic and obligate fungi. While berberine individually was effective against most of the fungi, Helminthosporium spp. were least affected even at the highest dose (1500 ppm). Santonin was equally effective against several fungi. Mixture of both alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 21 publications
2
10
0
2
Order By: Relevance
“…Nenaah (2010) found that the potentiality of the alkaloids of Peganum harmala as antibacterial and antifungal increased when tested as binary or total (crude) alkaloidal mixture, suggesting a kind of synergism and antagonism among these compounds. Singh et al (2001) also obtained similar results regarding the two alkaloids, berberine and santonin, isolated from the rhizomes of Berberis aristata and the flower buds of Artemisia maritima, respectively. They found that a mixture of both alkaloids was more effective.…”
Section: Cytogenetic Analysissupporting
confidence: 62%
“…Nenaah (2010) found that the potentiality of the alkaloids of Peganum harmala as antibacterial and antifungal increased when tested as binary or total (crude) alkaloidal mixture, suggesting a kind of synergism and antagonism among these compounds. Singh et al (2001) also obtained similar results regarding the two alkaloids, berberine and santonin, isolated from the rhizomes of Berberis aristata and the flower buds of Artemisia maritima, respectively. They found that a mixture of both alkaloids was more effective.…”
Section: Cytogenetic Analysissupporting
confidence: 62%
“…α-Santonin is known to be a potent anti-parasitic agent, and in its α,β forms exhibits anti-pyretic activity in a fashion similar to that of dopamine 1 . It is known to be effective against several species of fungi via the inhibition of spore germination 2 and hence is used as biocontrol agent. Chemically modifi ed derivatives of α-santonin are also known to confer the ability to induce the differentiation of human promyelocytic leukemia cells 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been used previously as an antiparasite preparation [7]. Other types of activity have recently been found for it, for example, antipyretic, anti-inflammatory, and fungicidal [8,9]. Santonin presents several reactive centers and is a convenient starting material for further chemical modification.…”
mentioning
confidence: 99%